Generation Chick: Reading Bridget Jones’s Diary, Jessica, 30., and Dies ist kein Liebeslied as Postfeminist Novels - Brenda Bethman (Studies in 20th & 21st Century Literature, 2011)
This article examines Helen Fielding’s, Marlene Streeruwitz’s, and Karen Duve’s novels in the context of the literarisches Fräuleinwunder, the generic conventions of chick lit, and postfeminism, relating all three to the globalization of the book publishing industry and its effects on German-language fiction. I argue that Duve’s and Streeruwitz’s texts can be understood as responses to the Anglo-American chick lit that flooded the German-language book market in the 1990s, of which Fielding’s novel is one of the best-known. Close readings situate both German-language novels firmly within the generic conventions of chick lit, and then look at the ways the texts relate to postfeminism, as well as second- and third-wave feminism. I conclude by arguing that our concept of Frauenliteratur should be expanded to include chick lit as well as more overtly political feminist texts.
Keywords: postfeminism; postfeminist novel; Helen Fielding; Marlene Streeruwitz; Karen Duve; literarisches Fräuleinwunder; chick lit; globalization; book industry; Anglo-American; German-language novels; Frauenliteratur